Strategic International Management: Text and Cases - Morschett, Dirk (Springer, 2015)
A compact overview of the most relevant concepts and developments in International Management. The various strategy concepts of internationally active companies and their implementation in practice are the core of this book. The authors describe the particularities of international value chain activities and management functions and offer a thorough understanding of how Production & Sourcing, Research & Development, Marketing, Human Resource Management and Controlling have to be designed in an international company and what models are available to understand those activities in an international context.